Exploring AI-Educator Co-Creation in Curriculum Design: Effects on Time Efficiency and Learning Outcomes - Zahraa Alkalefawi; Husnain Mukhdoom (Journal of Research in Education and Pedagogy, 2026)
Rapid adoption of Artificial Intelligence (AI) into the learning setting has dramatically altered the methods of curriculum design and the process of instructional planning. As technological efficiency and analytics of learners are often mentioned in modern studies, the actual experiences of the educators who take part in the process of co-creating the curriculum based on AI are rather under-researched. This qualitative phenomenological research examines the experiences of educators regarding the perception of AI as a co-developer of the curriculum, focusing specifically on the perceived time efficiency, the quality of instructions, and professional identity. The collection of data was performed with the help of semi-structured interviews with the participation of twelve educators and instructional designers who represented various institutional settings, including secondary schools, colleges, and universities. Thematic analysis showed that participants thought mostly that AI is an augmentative tool that facilitates the early phases of curriculum planning by lightening cognitive workload and speeding up structural drafting. The respondents also cited that the AI-generated recommendations helped to enhance the pedagogical fit and diversification of the instructional approaches; however, the quality of the meaningful curriculum remained left to contextual adaptation and professional judgment. Also, the interaction with AI systems was observed to promote more creative confidence and reflective pedagogical experimentation, and, at the same time, raise ethical transparency and over-reliance issues on automated outputs. The results highlight the fact that the successful implementation of AI in curriculum design is defined by a mutually beneficial co-creative relationship that does not undermine the agency of educators but uses the technological affordances. This work provides a contribution to the developing rhetoric in the adoption of responsible AI in the educational field with a focus on the relationships between human professionalism and intelligent systems.